Analisis Bisnis Menggunakan Business Model Canvas pada Bisnis Gipsum - Rizky Handayani; Catur Ariyanto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to examine business models in the gypsum sector by utilizing the Business Model Canvas (BMC) framework. The gypsum business is one of the fields that is growing rapidly in line with the increasing need for residential construction, building renovation, and aesthetic and functional interior design. However, to be able to survive and compete in an increasingly competitive market, gypsum business actors are required to have a business model that is structured, adaptive, and value-oriented for customers. This study uses a qualitative approach with a descriptive type of research. Data collection was carried out through in-depth interviews and direct observation of Nury Gipsum's business located in Klaten Regency. The results show that all nine elements in the Business Model Canvas, namely key partners, key activities, key resources, value offerings, customer relationships, distribution channels, customer segments, cost structure, and revenue streams, have been optimally implemented. Thus, the Business Model Canvas has proven to be effective in providing a comprehensive overview of business operations and can be a strategic basis for decision-making and gypsum business development in the future.